Cold agglutinin syndrome in a patient with human immunodeficiency virus infection - Abhilash Naini; Aakula Suguna Sree; Abhishek Venkata Nouduri; Sai Subrahmanyam Pappu; A Krishna Prasad (Journal of Clinical and Scientific Research, 2023)
A 44-year-old female with no prior comorbidities presented with a history of easy fatiguability and yellowish discolouration of eyes of 3 months duration. On examination, she had pallor and icterus. Jugular venous pressure was elevated. Earlier, the patient was diagnosed to have autoimmune haemolytic anaemia and was started on steroids 2 weeks ago elsewhere. Laboratory investigations showed severe anaemia, elevated mean corpuscular volume and lactate dehydrogenase levels. Corrected reticulocyte count was 2.5%. Unconjugated hyperbilirubinaemia was evident. Coomb's test was positive. In view of suspicion for cold agglutinin syndrome (CAS), monospecific agglutinin test with cold agglutinin titres was done, which tested positive. Serological testing was positive for human immunodeficiency virus (HIV) 1. The patient was diagnosed to have CAS secondary to HIV infection.